2009
DOI: 10.1073/pnas.0910080106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for insulin fibril assembly

Abstract: In the rare medical condition termed injection amyloidosis, extracellular fibrils of insulin are observed. We found that the segment of the insulin B-chain with sequence LVEALYL is the smallest segment that both nucleates and inhibits the fibrillation of fulllength insulin in a molar ratio-dependent manner, suggesting that this segment is central to the cross-␤ spine of the insulin fibril. In isolation from the rest of the protein, LVEALYL forms microcrystalline aggregates with fibrillar morphology, the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
394
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(424 citation statements)
references
References 44 publications
23
394
1
1
Order By: Relevance
“…However, AFM heights and TEM widths differ significantly in all samples in this study (Figs. S3, S4 and S5), even for insulin fibrils, for which previous studies suggested a helical arrangement of protofilaments (32). When this prevalent difference in measured heights and widths among fibrils is taken into consideration, a rectangular-cross-section model yields reliable and consistent values of I across different samples.…”
Section: Model For Fibril Cross Sectionsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, AFM heights and TEM widths differ significantly in all samples in this study (Figs. S3, S4 and S5), even for insulin fibrils, for which previous studies suggested a helical arrangement of protofilaments (32). When this prevalent difference in measured heights and widths among fibrils is taken into consideration, a rectangular-cross-section model yields reliable and consistent values of I across different samples.…”
Section: Model For Fibril Cross Sectionsmentioning
confidence: 82%
“…One fibril model of the HET-s peptide (37) and insulin (32) and two models of PrP fibrils (38,39) were stretched along the fibril axis, which allows determination of the modulus and strength from stress-strain curves (Figs. 3 A and S11 A).…”
Section: Correlation Between Nanomechanics and H-bond Densitiesmentioning
confidence: 99%
“…By identifying such peptide segments, a novel amylome analysis has recently been developed to predict the amyloidogenicity of proteins (50). The deep involvement of the steric zipper structure in the self-propagating ability has been supported by the inhibition of insulin fibrillation by an octapeptide coding amino acid sequence that forms a steric zipper (LVEALYLV) (51) and the effectiveness of the structure-based design of the peptide inhibitors of amyloid fibril formation for favorable affinity with the steric-zipper structure (52). Regarding the structural basis of cytotoxicity, the steric zipper structure is also more likely to intrude into biomembranes, resulting in cellular dysfunction, although the detailed roles of the steric zipper structure have not yet been elucidated.…”
Section: Candidates Of Specific Regions Contributing To the Propagatimentioning
confidence: 99%
“…Furthermore, short peptides (6 amino acids) from the A or B chain are able to form fibrillar aggregates on their own [110] and, under fibril forming conditions, they are protected from proteolysis and slowly exchange hydrogen with the solution at the amides along the peptide main chain [111]. More recently, an eight amino acid long peptide issued from the B chain, LVEALYLV, was shown to either inhibit or accelerate insulin aggregation, depending on the concentrations used [112]. The LVEALYLV peptide forms crystals where it is packed in parallel beta-sheets.…”
Section: 2mentioning
confidence: 99%
“…These beta sheets run in opposite directions along the 3D structure, interacting in an anti-parallel manner through hydrophobic and electrostatic interactions. Based on these findings and on X-ray analysis of the fibrils, a model of insulin aggregation was proposed, that suggests that the insulin LVEALYLV segments will form two parallel leaflets of anti-parallel beta sheets, forcing the rest of the structure to also adopt an extended β-sheet structure [112]. It is tempting to speculate that hydrophobic surfaces would mimic one of the leaflet and help the other one form, the surface facing the solution then acting as a template to grow other layers.…”
Section: 2mentioning
confidence: 99%